The Comparison of Risky Decision Making in Opium Abuser and Healthy Matched Individuals - Vahid Nejati; Esmaeel Shiri; Fahimeh Doostmohammadi; Bahareh Barzegar; Zahra Mohammadifard (Drug Control Headquarters, Research and Education Office, 2013)
Objective: Risky decision making is one of the most basic mechanisms of impulsive and addictive behaviors. The purpose of present study was the comparison of risky decision making in opium abuser and healthy matched individuals. Method: In present cross sectional study, 50 opium abusers compared to 50 healthy who were matched on age and gender. Balloon Analogue Risk Taking Task was used for evaluation of risk taking in participant of both groups. Results: The results showed that opium abusers have had higher scores on number of plumbing balloon and exploded balloon in BART task than normal individuals. Conclusion: Opium abusers have higher risk taking than normal individuals.